Stunning Effects after a Diagnostic Dose of Iodine-131 - Kao, Chia-Hung; Yen, Tzu-Chen (Nuklearmedizin - NuclearMedicine, 1998)
Aim: To understand stunning effects of a diagnostic dose of iodine-131 (1-131). Methods: Four hundred and sixty-eight patients (101 males, 367 females, ages: 6-75 years) with well differentiated thyroid cancer, following total or nearly total thyroidectomy, were studied. One hundred and eleven MBq (3 mCi) diagnostic (Dx) doses of 1-131 whole body scan (WBS) were obtained after withholding thyroxine after 6 weeks and triiodothyronine for 2 weeks. One week to one month later, 3.7-7.4 GBq (19854-200 mCi) 1-131 was given to them, then a therapeutic (Tx) dose of 1-131 WBS was performed. The serum thyroid simulating hormone level was usually above 30 ulU/ml. Results: Of the 468 patients, 344 (73.5%) had scintigraphic patterns of apparently decreased uptake in 240 thyroid remnants and 104 metastatic lesions on the Tx dose of 1-131 WBS compared to Dx dose of 1-131 WBS. Stunning phenomenon occured in 50 cases, including 42 thyroid remnants and 18 metastatic lesions. Conclusion: Dx dose of 1-131 may influence the uptake of a subsequently administered Tx dose of 1-131.
Keywords: Stunning effects; diagnostic dose; 1-131